Physicocemical and Microbiologycal Characterization of Hydroxyapatite Based Toothpaste From Freshwater Mussel (Pilsbryoconcha exilis) Shell - Octavia, Stephanie; Sidauruk, Santhy Wisuda; Sari, Noor Ira (Aquatic Life Sciences, 2025)
Utilizing freshwater mussel shell waste as a sustainable source of calcium-based biomaterials represents an eco-friendly approach to producing hydroxyapatite for oral care applications. Hydroxyapatite acts as an active component in toothpaste formulations, functioning as an abrasive and inhibiting bacterial growth responsible for dental plaque. This study aimed to evaluate the effect of adding hydroxyapatite to toothpaste on its physicochemical and microbiological characteristics and to determine the best formulation of freshwater mussel shell–based hydroxyapatite toothpaste. The research included hydroxyapatite synthesis, toothpaste production, and evaluation of physicochemical and microbiological properties. An experimental method using a completely randomized design was employed, consisting of four treatments: TH35 (35% hydroxyapatite), TH45 (45% hydroxyapatite), TH55 (55% hydroxyapatite), and TK (commercial toothpaste). The results showed that the addition of hydroxyapatite significantly affected the physicochemical characteristics (color, aroma, texture, homogeneity, spreadability, pH, and foam height) and microbiological activity (inhibition zone against Staphylococcus aureus) at a 95% confidence level (p < 0.001). The best formulation, based on pH, calcium content, and bacterial inhibition zone, was obtained with 55% hydroxyapatite, having a pH of 7.39, calcium content of 15.97%, and an inhibition zone of 22.24 mm against Staphylococcus aureus. These findings demonstrate that mussel shell–derived hydroxyapatite can serve as a sustainable and functional ingredient in toothpaste formulations with enhanced antibacterial and physicochemical performance.